2017
DOI: 10.3389/fpsyg.2017.00466
|View full text |Cite
|
Sign up to set email alerts
|

Video Games Exposure and Sexism in a Representative Sample of Adolescents

Abstract: Research has indicated that many video games are saturated with stereotypes of women and that these contents may cultivate sexism. The purpose of this study was to assess the relationship between video game exposure and sexism for the first time in a large and representative sample. Our aim was also to measure the strength of this association when two other significant and well-studied sources of sexism, television exposure and religiosity, were also included in a multivariate model. A representative sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 64 publications
1
27
0
3
Order By: Relevance
“…Begue et al 2017 public-health level effects of video games that cannot be supported by data from their studies.…”
Section: Dill 2007mentioning
confidence: 65%
“…Begue et al 2017 public-health level effects of video games that cannot be supported by data from their studies.…”
Section: Dill 2007mentioning
confidence: 65%
“…Helfgott 2015, p. 59 "Research has indicated that many video games are saturated with stereotypes of women and that these contents may cultivate sexism." Bégue et al 2017 same mistakes as that for VVG research. Most pronounced among these is the tendency for some scholars to irresponsibly make claims that go beyond the data and exaggerate the potential harms of video games.…”
Section: Dill 2007mentioning
confidence: 84%
“…Indeed, surveys of scholars began to lean more toward skepticism, with various surveys finding that only approximately 10-39.5% (Ferguson 2015b, Ferguson & Colwell 2017, Quandt et al 2015 of scholars and clinicians agreed that media or video game violence could contribute to societal aggression or violence. Some scholars associated with antimedia advocacy (e.g., Bushman et al 2015) tried to claim a consensus anyway, although these efforts were subsequently criticized for being misleading (e.g., Etchells & Chambers 2014. Agree there is a causal relationship between exposure to violent media and aggression (Bushman et al 2015) Agree violence in the media is a major factor in real-life violence (Bushman et al 2015) Clinicians who work with youth who agree violent video games cause youth violence (Ferguson 2015b) Scholars who agree violent video games cause youth assaults (Ferguson & Colwell 2017) Agree the effects of digital games on aggression are a problem for society (Quandt et al 2015) Agreement among scholars and clinicians (%)…”
Section: Scholarly Viewsmentioning
confidence: 99%
“…To date, this is one of very few longitudinal designs on this topic. In a later study, Bègue, Sarda, Gentile, Bry, and Roché () found a statistically significant but arguably trivial impact on sexism for video game playing ( r = 0.07), but no impact of television.…”
Section: Introductionmentioning
confidence: 89%